The solution focused approach with children and young people : current thinking and practice - Yusuf, Denise (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Solution Focused Approach with Children and Young People: Current Thinking and Practice brings together leading figures and innovative practitioners from different professions, contexts and countries to provide a unique overview of Solution Focused work with children and young people. Presenting a range of applications in individual, group and community work, it puts the spotlight on diverse fields, exploring how the Solution Focused approach can work in real-world contexts"--
OCLC-licensed vendor bibliographic record.
Keywords: Solution-focused therapy for children; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health